Satisfaction as a Mediator and Its Interaction With Adherence to Labor Analgesia Protocols: A Cross-Sectional Survey of Chinese Medical Personnel - Lang, Dong; Long, Chengxu; Lin, Shuna; Xie, Yinghua; Chen, Fangfei; Zhao, Rui; Liu, Chunping; Tang, Shangfeng (Frontiers in Public Health, 2022)
Background Although the Chinese promotion of labor analgesia began in 2018 to improve maternal health, high-quality medical care is difficult to provide to pregnant women when medical staff cannot implement standard labor analgesia procedures. This study aims to examine medical personnel's adherence to labor analgesia protocols and to explore the relationships among adherence, satisfaction, and other factors. Methods The data were from a national cross-sectional dataset (N = 13,944) of the 2020 Chinese Labor Analgesia Pilot Evaluation Project. Mediating and moderating effects analyses were used to examine the role of satisfaction as a mediator between support measures and adherence. Results There were differences in adherence between different types of medical personnel. Support measures and satisfaction had a positive association with adherence to labor analgesia protocols. Satisfaction had a significant mediating and moderating effect on the relationship between support measures and adherence to labor analgesia standards. Moderating effects of professional titles and attitudes were also observed. Conclusion Primary health care policies worth considering include comprehensive incentives for medical institutions to improve the use of labor analgesia by medical personnel. It is also worth considering providing more training opportunities for the staff in anesthesiology departments.